Developing Financial Inclusion Strategies through Technology and Policy to Improve Energy Access for Underserved Communities - Ezinne C. Chukwuma-Eke; Olakojo Yusuff Ogunsola; Ngozi Joan Isibor (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Access to affordable and reliable energy remains a significant challenge for underserved communities, particularly in developing regions. Financial constraints, lack of investment, and inadequate policy frameworks hinder the widespread adoption of modern energy solutions. This paper explores the role of financial inclusion strategies, driven by technology and policy interventions, in improving energy access for marginalized populations. By integrating digital financial services, decentralized energy systems, and innovative policy measures, this study proposes a comprehensive framework to bridge the energy gap. The proposed framework focuses on leveraging financial technology (FinTech), mobile banking, and blockchain-based microfinancing to enhance accessibility to clean energy solutions. Digital payment platforms and mobile-based credit scoring models facilitate microloans for renewable energy adoption, empowering low-income households and small enterprises. Blockchain technology ensures transparency, security, and accountability in financial transactions, reducing the risks of fraud and inefficiencies in energy financing. Policy interventions play a crucial role in fostering financial inclusion and energy accessibility. Targeted subsidies, regulatory reforms, and public-private partnerships are essential for creating an enabling environment. Governments and financial institutions must collaborate to design policies that incentivize investment in decentralized energy projects, such as mini-grids and off-grid solar solutions. Additionally, carbon credit markets and green bonds can provide sustainable financing mechanisms for long-term energy development. A case study analysis highlights successful implementations of technology-driven financial inclusion models in regions with limited energy access. Results demonstrate that integrating mobile financial services and decentralized energy solutions leads to increased energy affordability, economic empowerment, and improved quality of life. The findings underscore the need for a multi-stakeholder approach, combining technological innovation, policy support, and community engagement to drive sustainable energy inclusion. This study contributes to the discourse on financial inclusion and energy sustainability by proposing a data-driven and policy-oriented approach. Future research should explore the scalability of digital financial services in emerging markets and the long-term impact of financial inclusion strategies on energy equity.
Keywords: Financial Inclusion; Energy Access; Underserved Communities; FinTech; Blockchain; Microfinance; Renewable Energy; Policy Interventions; Digital Payment Systems; Sustainable Development